Megacities Vs Global Cities: Development and Institutions - Jean-Marie Huriot; Lise Bourdeau-Lepage (European Regional Science Association (ERSA), 2006)
In a preceding paper (Louvain Economic Review), we define city globalization as the process by which a city gains the ability to coordinate complex economic activities at a global scale. The resulting "global cities" carry out the functions of design, decision and control in the global economy. However, the logic of city globalization is not universal. It does not apply equally to different regions in the world. A large part of the less developed countries (LDCs) remains at the margin, despite the dramatic growth of its major cities, especially the "large urban agglomerations" and the "megacities" as defined by the United Nations. In 2003, 15 of the world's 20 megacities were located in LDCs. We stress the differentiation of the city globalization process and the possible divergence between city size and city globalization, i.e. between global cities and mega-cities. We propose some avenues for explaining this divergence. We use both statistical and theoretical arguments based on the economic theory of agglomeration (Fujita and Thisse), the theory of world cities (Friedman, Sassen, Taylor and GaWC) and the theory of institutions (North). In a large part of the literature, it is considered that a large city can more probably become a global city than a smaller one, because city size favors the diversity of activities, a high level of human capital, of communication equipments, and ability to benefit from increasing returns. However, this logic is not universal. City size is neither a necessary nor a sufficient condition of city globalization. It appears that the level of development of the country gives only a partial explanation of the divergence. The ability to coordinate complex activities at a global scale, which characterize global cities, depends closely on the nature and the quality of institutions. The bad quality of governance, the low level of social connectivity (Sassen), the high level of corruption, are important obstacles to city globalization in LDCs. The existence of an important informal sector can explain that cities in LDCs beyond the size compatible with their economic resources and with their ability to generate externalities favorable to city globalization
Keywords: 330